Responding to Omicron: Speaker Commitment and Legitimisation in COVID-related Press Conferences - Szczyrbak, Magdalena; Tereszkiewicz, Anna (Studies in Polish linguistics, 2023)
This paper examines the ways in which New Zealand and Polish government officials communicated the easing of COVID restrictions to the general public. The study aimed to identify legitimising strategies used to justify the lifting of restrictions and related measures, and to establish how agency and responsibility were discursively constructed in the subgenre of political press conference in two different socio-political settings. Informed by the notions of legitimisation (Chilton 2004), speaker commitment and stance (Marín Arrese 2011, 2015, 2021), the research looked into the linguistic marking of effective stance (deonticity, assessments, attitudinals and directives) and epistemic stance (epistemic modality, truth-factual validity as well as experiential, cognitive and communicative stance), considering both the subjectivity/intersubjectivity dimension and the explicitness/implicitness of the speaker’s role. In addition, the study considered the key discursive strategies used to (de)construct agency in the discourses of NZ and Polish policymakers seen as proponents of divergent public health policies. As the findings indicate, the Polish officials conveyed chiefly experiential stance and projected less involvement, whereas the NZ Prime Minister favoured cognitive stance and deonticity as well as direct appeals to the audience. The analysis shows that the speaker’s (dis)identification with the respective policy finds reflection in the varying degrees of speaker commitment and the (de)construction of agency.